Nitrogen source and fate of typical orchard with gentle slope in semi-arid areas - An, Miaoying; Xie, Ying; Han, Yuguo; Zhou, Jinxing; Guo, Hulin; Qu, Zhixu (International Journal of Agricultural and Biological Engineering, 2024)
Excessive nitrogen (N) exports caused by human activities are one of the main reasons for the numerous environmental problems in agricultural production. Orchards, as an essential part of agricultural production, play a crucial role in rural economic development and ecological environment construction. Understanding the migration pathways of N in orchards is significant for the scientific management of orchards and the reduction of environmental pollution. In this research, the source and fate of N in a typical orchard in Beijing were quantitatively analyzed. N management strategies were proposed in combination with agricultural production habits. The total N input into the orchard was 487.19 kg/hm2·a, of which 85.44%, 10.99%, 3.30% and 0.27% of N input were from fertilizer application, atmospheric deposition, biological N fixation and pesticide, respectively. A large amount of N fertilizer application was the primary source of N input in the orchard. For the N fate, the N surplus in the soil could reach up to 68.40% of total N inputs, and only 20.16% were absorbed and utilized by plants. The amount of N losses through ammonia volatilization, runoff and sediment, nitrification and denitrification accounted for 10.68%, 0.39% and 0.37%, respectively. N input in the orchard mainly remained in soil, while N loss was mainly through ammonia volatilization. There were 176.72, 99.00, and 57.52 kg/hm2·a N surplus in 0-40 cm, 40-80 cm, and over 80 cm soil layers, respectively. To deal with the N accumulation on the soil surface and the migration of N from the soil surface to the deep layer of orchards, reducing N fertilizer application, substituting circular furrow for the whole orchard fertilization, adjusting irrigation schedule by reducing the amount of single irrigation, increasing the frequency of irrigation to three times in the normal year, and adopting efficient water-saving irrigation technology are realizable methods. Keywords: gentle slope orchard, N accumulation-migration, N fate, N source, semi-arid areaDOI: 10.25165/j.ijabe.20231606.7701Citation: An M Y, Xie Y, Han Y G, Zhou J X, Guo H L, Qu Z X. Nitrogen source and fate of typical orchard with gentle slope in semi-arid areas. Int J Agric & Biol Eng, 2023; 16(6): 167–175.